Story construction by abused children through repeated read-alouds of therapeutic metaphors - Aligada, Rosario Margarita A. (2007)
Therapeutic Metaphors were used during bibliotherapy sessions for physically or sexually abused children. This research aimed to investigate how abused children made sense to therapeutic metaphors which were read to them repeatedly during bibliotherapy sessions as seen from the stories they created in response to the therapeutic metaphor read-alouds. The literary events were viewed from the characteristics of the children's written texts, the process by which the writers produced the texts, and the process by which readers made sense of the texts. The grounded theory of story construction by abused children arose from the five aspects displayed in the created texts. These aspects are language, structure of text, content, use of reason, and mode of response. Story construction is an individual, subjective, reflective process that involves dynamic decision-making in these aspects.
"October 2007."
Vita.
Thesis (Ph.D. Reading Education)--University of the Philippines, Diliman.
Keywords: Abused children -- Philippines -- Manila Metropolitan Area -- Language; Bibliotherapy for children -- Philippines -- Manila Metropolitan Area; Child abuse -- Philippines -- Manila Metropolitan Area